Mutually inclusive mechanisms of drought‐induced tree mortality - Peter Hajek; Roman M. Link; Charles A. Nock; Jürgen Bauhus; Tobias Gebauer; Arthur Gessler; Kyle Kovach; Christian Messier; Alain Paquette; Matthias Saurer; Michael Scherer‐Lorenzen; Laura Rose; et al. (Global Change Biology, 2022)
Unprecedented tree dieback across Central Europe caused by recent global change‐type drought events highlights the need for a better mechanistic understanding of drought‐induced tree mortality. Although numerous physiological risk factors have been identified, the importance of two principal mechanisms, hydraulic failure and carbon starvation, is still debated. It further remains largely unresolved how the local neighborhood composition affects individual mortality risk. We studied 9435 young trees of 12 temperate species planted in a diversity experiment in 2013 to assess how hydraulic traits, carbon dynamics, pest infestation, tree height and neighborhood competition influence individual mortality risk. Following the most extreme global change‐type drought since record in 2018, one third of these trees died. Across species, hydraulic safety margins (HSMs) were negatively and a shift towards a higher sugar fraction in the non‐structural carbohydrate (NSC) pool positively associated with mortality risk. Moreover, trees infested by bark beetles had a higher mortality risk, and taller trees a lower mortality risk. Most neighborhood interactions were beneficial, although neighborhood effects were highly species‐specific. Species that suffered more from drought, especially Larix spp. and Betula spp., tended to increase the survival probability of their neighbors and vice versa. While severe tissue dehydration marks the final stage of drought‐induced tree mortality, we show that hydraulic failure is interrelated with a series of other, mutually inclusive processes. These include shifts in NSC pools driven by osmotic adjustment and/or starch depletion as well as pest infestation and are modulated by the size and species identity of a tree and its neighbors. A more holistic view that accounts for multiple causes of drought‐induced tree mortality is required to improve predictions of trends in global forest dynamics and to identify mutually beneficial species combinations.